Diversity and distribution of polypores in the moist deciduous forests of Peechi-Vazhani wildlife sanctuary, Kerala - Muhammed Iqbal A (Department of Forest Management and Utilisation, College of Forestry, 2015)
The study entitled “Diversity and distribution of polypores in the moist deciduous forests of Peechi-Vazhani Wildlife Sanctuary, Kerala” was carried out with the objectives to find out the diversity, distribution and host preference of polypores in the moist deciduous forests of Peechi-Vazhani Wildlife Sanctuary during three different seasons. An attempt has also been made to find out the effect of substrate features like diameter, type and decay class on the diversity and abundance of polypores. Three fixed size permanent sample plots of 100 m×100 m were established in three different locations and these permanent plots were enumerated during three different seasons to collect information on influence of seasonal fluctuation in fruitbody production and details on substratum. Apart from the plot based sampling, opportunistic sampling method was also adopted to maximize the documentation of polypore fungal diversity and distribution. A total of thirty six species were recorded from the sanctuary and among this Pycnoporus cinnabarinus and Datronia mollis were the first report from South India. Out of this, white rot fungi contributed 94.44 per cent and 5.56 per cent were brown rot fungi. The density and frequency of occurrence have been varied significantly during different seasons and the community structure and species composition during monsoon and post monsoon season were distinct from pre-monsoon season. However, fungal diversity analysis showed that species richness was higher during monsoon season and revealed the influence of seasonal variation on fungal diversity. The high species similarity was observed between monsoon and post monsoon season compared to pre-monsoon and monsoon. A total of 17 host tree species were identified in ten different families and Terminalia paniculata was found to be highly preferred by polypores. Polypores like Fulvifomes nilgheriensis and Fuscoporia senex were found to be host specific and were found only on Xylia xylocarpa. The maximum fungal density has been recorded in host trees with 21-<30 cm diameter class. Among the substrate types, maximum number of individuals was observed on trunk and living trees supported only very few polypores. The newly emerged species during monsoon season showed more association with decay class 2 and the decay class association of some species remained unchanged during all the seasons. The conceptual framework on primary ecological strategy revealed that polypores exhibits ruderal, combative and stress tolerant behaviours. The present study concluded that the diversity and distribution of polypores are determined by seasonal fluctuations and substrate features.